Polymorphic variants of the HSD11B1 gene may be involved in adverse metabolic effects of glucocorticoid replacement therapy in Addison's disease - Fichna, Marta; Żurawek, Magdalena; Gryczyńska, Maria; Sowińska, Anna; Nowak, Jerzy; Ruchała, Marek (European journal of internal medicine, 2016)
Increased frequency of glucose intolerance, dyslipidaemia, and obesity has been reported in subjects treated for adrenocortical failure (Addison's disease, AD). Glucocorticoid substitution is difficult to adjust and patients display variable responses to steroid dosage. Since local regeneration markedly contributes to the available cortisol pool, the activity of 11β-hydroxysteroid dehydrogenase type 1 (HSD11B1 gene) may be involved in adverse metabolic profile. Our aim was to explore if HSD11B1 polymorphisms might impact on individual requirements for glucocorticoid replacement and its metabolic effects. This cross-sectional analysis comprised 152 AD patients (aged 47.1±15.1years) receiving regular glucocorticoid substitution. Their daily hydrocortisone dosage (mean 25.5±5.5mg) had been based upon clinical features. Stratification by the HSD11B1 genotypes (rs846910, rs3753519 and rs12086634) enabled comparisons with regard to patients' anthropometric, hormonal, and metabolic characteristics. In rs3753519-stratified analysis, carriers of the minor allele presented significantly increased BMI (p<0.001), fasting plasma glucose (p<0.001) and HOMA-IR (p=0.021) compared to the wild-type homozygotes, although the HOMA-IR association disappeared when adjusted for age, gender, BMI, and hydrocortisone dose. In contrast, homozygous carriers of two common rs12086634 alleles displayed elevated serum triglycerides (p=0.035), total, and LDL cholesterol (p=0.001 and 0.003, respectively) but only total cholesterol association survived after correction for multiple comparisons. Finally, no association of rs846910 with any clinical or laboratory parameter was found. Our study provides support for plausible implication of the HSD11B1 polymorphisms in susceptibility to develop undesirable effects of glucocorticoid replacement. Further analyses are warranted to validate the role of HSD11B1 variants in clinical practice. •Increased cardiometabolic risk is an issue in glucocorticoid replacement therapy.•Functional variants of HSD11B1 may enhance the undesirable effects of hydrocortisone.•Rs3753519 minor allele is associated with increased BMI and fasting plasma glucose.•Rs12086634 wild-type allele associates with elevated cholesterol level.